2016
DOI: 10.1142/s0129065716500313
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Biosignal Analysis for Epileptic Seizure Monitoring

Abstract: Persons who suffer from intractable seizures are safer if attended when seizures strike. Consequently, there is a need for wearable devices capable of detecting both convulsive and nonconvulsive seizures in everyday life. We have developed a three-stage seizure detection methodology based on 339 h of data (26 seizures) collected from 10 patients in an epilepsy monitoring unit. Our intent is to develop a wearable system that will detect seizures, alert a caregiver and record the time of seizure in an electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 44 publications
1
83
0
Order By: Relevance
“…Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these. 26,27 Describing the influence of an ultra-long-term EEG monitoring device on the mobility of the wearer is a key aspect of its usability. In 2017, Bateson et al 28 developed a mobility score for use in wearable EEG research going from 0 (least mobile) to 5 (most mobile).…”
Section: Discussionmentioning
confidence: 99%
“…Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these. 26,27 Describing the influence of an ultra-long-term EEG monitoring device on the mobility of the wearer is a key aspect of its usability. In 2017, Bateson et al 28 developed a mobility score for use in wearable EEG research going from 0 (least mobile) to 5 (most mobile).…”
Section: Discussionmentioning
confidence: 99%
“…A study with an Empatica E3 wristband reported that 97% of 34 predominantly non-motor seizures could be detected with a hierarchical classifier based on EDA 36 . However, using mainly EDA dramatically decreased specificity; thus, information from other physiological signals is necessary to detect non-convulsive seizures, such as heart rate and arterial oxygenation 41 .…”
Section: Limits and Future Workmentioning
confidence: 99%
“…36 However, using mainly EDA dramatically decreased specificity; thus, information from other physiological signals is necessary to detect nonconvulsive seizures, such as heart rate and arterial oxygenation. 41 Finally, a seizure detector incorporating EDA could be suitable for other important applications, such as identifying triggering factors reflected in autonomic activations (e.g., stress or deep sleep) or using EDA biofeedback for training patients to prevent epileptic seizures. 42…”
Section: Limits and Future Workmentioning
confidence: 99%
“…Epileptic seizures are potentially dangerous as they can lead to complications, including injury, status epilepticus, and sudden unexpected death in epilepsy (SUDEP) [ 1 ]. Adequate seizure detection may have the potential to minimize these complications and to ameliorate treatment evaluation, as seizures—particularly those at night—are often underreported [ 2 – 5 ]. Detection devices may also help to improve the independence and quality of life of people with epilepsy and their caregivers [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%